IMPROVEMENT OF WORK METHOD TO REDUCE REPETITIVE WORK IN PT. TRIJAYA PLASTIK UTAMA WITH OCRA METHOD - Bambang Suhardi; Syafiya Maharani; Rahmaniyah Dwi Astuti (Spektrum Industri, 2020)
PT. Trijaya Plastik Utama is a company that manufactures raincoats. Based on the results of interviews with workers in 3 production departments, most experienced complaints in the upper limbs, especially the neck, back, and hands. Most of the work does repetitive activities with long cycles, so the nature of the work is suspected to cause musculoskeletal disorders for the operator. This study aims to identify the presence of musculoskeletal risks due to repetitive work using the Occupational Repetitive Action (OCRA) method. Based on the identification results of each department section, the packing section has the highest OCRA index value with a value of 3.86 for the right hand and 3.01 for the left hand. Improvement efforts to reduce risk due to repetitive work is to apply the concept of Eliminate, Combine, Re-Arrange and Simplify (ECRS) and the proposed design of work facilities. As a result, the OCRA index value dropped to 0.95 for the right hand and 0.85 for the left hand where the conditions were optimal